Coordination‐Induced Interlinked Covalent‐ and Metal–Organic‐Framework Hybrids for Enhanced Lithium Storage. Issue 37 (4th August 2019) - Sun, Weiwei; Tang, Xuxu; Yang, Qinsi; Xu, Yi; Wu, Fan; Guo, Siyu; Zhang, Yanfeng; Wu, Minghong; Wang, Yong
Abstract: Covalent organic frameworks (COF) or metal–organic frameworks have attracted significant attention for various applications due to their intriguing tunable micro/mesopores and composition/functionality control. Herein, a coordination‐induced interlinked hybrid of imine‐based covalent organic frameworks and Mn‐based metal–organic frameworks (COF/Mn‐MOF) based on the MnN bond is reported. The effective molecular‐level coordination‐induced compositing of COF and MOF endows the hybrid with unique flower‐like microsphere morphology and superior lithium‐storage performances that originate from activated Mn centers and the aromatic benzene ring. In addition, hollow or core–shell MnS trapped in N and S codoped carbon (MnS@NS‐C‐g and MnS@NS‐C‐l) are also derived from the COF/Mn‐MOF hybrid and they exhibit good lithium‐storage properties. The design strategy of COF–MOF hybrid can shed light on the promising hybridization on porous organic framework composites with molecular‐level structural adjustment, nano/microsized morphology design, and property optimization. Abstract : Based on the coordinated interaction between CN groups from covalent organic frameworks and Mn ions of metal–organic frameworks, a coordination‐induced interlinked hybrid of COF/Mn‐MOF is designed with flower‐like morphology. A synergistic effect relative to new active sites for lithium storage endows it with superior application performance. Hollow or core–shell microspheres of MnS@N/S codoped carbons can also be derived with superior electrochemical properties.